2019
DOI: 10.1111/hepr.13317
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A‐coupled liposomal Rho‐kinase inhibitor ameliorates liver fibrosis without systemic adverse effects

Abstract: Aim Rho‐kinase (ROCK) inhibitor could ameliorate liver fibrosis by suppressing hepatic stellate cell (HSC) activation. However, because systemic administration of ROCK inhibitor causes serious adverse effects, we developed a drug delivery system selectively delivering ROCK inhibitor to HSCs. Here, we examined whether our developed vitamin A (VA)‐coupled liposomal ROCK inhibitor reduced liver fibrosis in rats without causing systemic adverse effects. Methods LX‐2 HSCs were analyzed for morphological changes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Later studies confirmed that Rho-kinase signaling regulates HSC activation and migration [ 146 , 147 , 148 ]. Several other studies demonstrated the beneficial effects of selective delivery of Rho kinase inhibitor to HSCs on the development of hepatic fibrosis in vivo [ 146 , 149 , 150 , 151 ].…”
Section: Camp Signaling In Aldmentioning
confidence: 99%
“…Later studies confirmed that Rho-kinase signaling regulates HSC activation and migration [ 146 , 147 , 148 ]. Several other studies demonstrated the beneficial effects of selective delivery of Rho kinase inhibitor to HSCs on the development of hepatic fibrosis in vivo [ 146 , 149 , 150 , 151 ].…”
Section: Camp Signaling In Aldmentioning
confidence: 99%
“…As attenuated fibrosis in response to ROCK1/2 inhibition was shown to be associated with HSC inactivation 38 and cell-intrinsic ROCK signalling in HSCs drives α-SMA and collagen expression, 39 more recent studies have focused on HSC-targeted delivery of ROCK inhibitors as a therapeutic strategy. 40 , 41 In these studies, the ROCK pathway was confirmed a targetable driver of liver fibrosis in multiple settings and the contribution of cell-intrinsic ROCK signalling in HSCs was demonstrated. However, the contribution of ROCK signalling in upstream immune mediators, and the specific role of ROCK2, the isoform shown to drive pathogenic T-cell, 12 , 42 B-cell, 43 and macrophage 20 differentiation, in liver fibrosis has not previously been established.…”
Section: Discussionmentioning
confidence: 94%
“…Nonspecific ROCK1 inhibitors fasudil and Y-27632 demonstrate inhibitor pharmacotherapy is beneficial for these diseases; however, adverse effects such as hypotension, insulin resistance, and obesity are observed when ROCK expression/activity is non-specifically altered or systemically downregulated ( 25 , 32 35 , 62 , 63 ). This once again highlights the importance of tissue-specific targeting of ROCK1, for example, via mannose-6-phosphate carriers ( 62 , 64 , 65 ), vitamin-A-coupled lysosomes ( 66 ), or genetic engineering. Overall, these tissue-specific approaches will greatly facilitate deciphering the many critical metabolic functions of ROCK1 and, ultimately, may result in the development of novel treatments for metabolic 2974disorders.…”
Section: Discussionmentioning
confidence: 94%